New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil - FERREIRA NETTO, André Luiz (Universidade Federal do Pará, 2019)
A new species of Pyrrhulina is described based on 60 specimens from tributaries of the rio Amazonas: rio Anapu, rio Capim, rio Guamá and rio Xingu, and coastal drainages in the state of Pará, Brazil. The new species differs from all congeners by having the primary stripe (the horizontal stripe of dark pigmentation extending posteriorly from the snout) terminating at the distal edge of the opercle. In all other species of Pyrrhulina, the primary stripe is either restricted to the snout or continues beyond the head (i.e. at least the anteriormost four scales of the lateral line series).